Challenging Social Capital to Develop Community-based Digital Economy Platform in the Traditional Market - Suyatna, Hempri; Farransahat, Matahari; Firdaus, Rindu; Indroyono, Puthut; Wibowo, Istianto Ari (Journal of Social Development Studies, 2024)
A private and large corporation typically owns and manages the digital platform, positioning merchants in traditional markets solely as providers of goods. This practice distances merchants from additional advantages offered by the platform and excludes them from the decision-making process. This paper explores the strength of social capital in enhancing opportunities for small economic actors, such as merchants in traditional markets, to benefit from the digital economy through a community-based online market platform, thus overcoming this challenge. Employing a qualitative descriptive research method with a case study approach, data were obtained through interviews, documentation, and focus group discussions. This paper demonstrates that social capital mitigates the challenge of financial capital in leveraging digital economy innovations, enriching the discourse on the interconnectedness between social relations and economic development in community-based settings like traditional markets.